The Legal Psychology Approach in Handling Juvenile Delinquency (An Analysis of the Causes of Legal Violations Among Juvenile Offenders at the Cileungsi Social Institution) - Ulwan, Muhamad; Fuad, Fokky; Machmud, Aries (Universitas Muhammadiyah Tangerang, 2025)
The changing times and the development of children significantly influence their behavior, ultimately raising concerns among perpetrators, victims, parents, and the broader community. Adolescents are particularly vulnerable to social and psychological pressures, which often affect their decisions and actions. Juvenile delinquency reflects non-compliance with prevailing rules and norms, whether within the family, school, community, or the individual themselves. Therefore, it is essential to instill these norms in adolescents from an early age to foster proper understanding. This study aims to identify adolescents in conflict with the law from the perspective of legal psychology. The research employs a normative juridical approach, with qualitative data analysis conducted through a literature review. The study involves examining, understanding, identifying, and recording literature, legislation, and relevant data concerning the issues under investigation. The findings indicate that addressing juveniles in conflict with the law requires a specific legal psychology approach to analyze the underlying causes of offenses and the contributing factors leading adolescents to become juvenile offenders.Keywords: Children, Juvenile Delinquency, Psychology in Law.